Síntese, caracterização e aplicação de solventes eutéticos em reações envolvendo formação ou derivatização de heterociclos - Paveglio, Guilherme Caneppele (2016)
This work describes the synthesis, characterization and application of eutectic solvents in reactions involving heterocycles. The chosen solvents consisted of a eutectic mixture of choline chloride (ChCl) with different Hydrogen Bonding Donor (HBD) especies such urea, glycerol, ethylene glycol, ptoluenesulfonic acid and malonic acid. The characterization of the eutectic solvent was carried out using Nuclear Magnetic Resonance (1H, 13C, 35Cl) and thermal analysis (DSC and TGA). Initially, the eutectic solvents were used as solvent in the synthesis of triazolopyrimidines by cyclocondensation reaction between β-enaminones and 3-amino-5-methylthio-1H-1,2,4-triazole, which eight new compounds was synthesized. In the next step, the eutectic solvents were applied in three types of organic reactions using oil bath and microwave irradiation as activation method. It is noteworthy that this is the first work in which DES were used as solvents in synthesis using microwave. The three chosen reactions were: a) Cyclocondensation involving tert-butylhydrazine hydrochloride and β- enaminones, wherein the solvent that showed the best results in oil bath was ChCl:Malonic acid (1:2) and microwave was ChCl: Urea (1:2); b) Aliphatic Nucleophilic substitution involving 3,5-dimethyl-1Hpyrazole with alkylating primary or secondary. The best result in both oil bath and microwave was obtained when the mixture ChCl:Ethylene glycol (1:1) was used. c) 1,3-dipolar cycloaddition involving benzyl azide and phenylacetylene. The most efficient solvent in both oil bath and microwave was ChCl:Ethylene glycol (1:2). The last step of these work consisted to application of eutectic solvents in the synthesis of 4-acyl-1-aryl (alkyl)-1,2,3-triazole by 1,3-dipolar cycloaddition reaction between β- enaminones and organic azides in oil bath. In this synthesis, eleven compounds were synthesized, which 5 are unpublished. This work shows that the eutectic solvents can be widely used in the synthesis of heterocyclic compounds both oil bath and microwave methods.